Synthesis, Structure and Antimicrobial Properties of Novel Benzalkonium Chloride Analogues with Pyridine Rings - Brycki, Bogumił (Molecules, 2017)
Quaternary ammonium compounds (QACs) are a group of compounds of great economic significance. They are widely used as emulsifiers, detergents, solubilizers and corrosion inhibitors in household and industrial products. Due to their excellent antimicrobial activity QACs have also gained a special meaning as antimicrobials in hospitals, agriculture and the food industry. The main representatives of the microbiocidal QACs are the benzalkonium chlorides (BACs), which exhibit biocidal activity against most bacteria, fungi, algae and some viruses. However, the misuses of QACs, mainly at sublethal concentrations, can lead to an increasing resistance of microorganisms. One of the ways to avoid this serious problem is the introduction and use of new biocides with modified structures instead of the biocides applied so far. Therefore new BAC analogues P13–P18 with pyridine rings were synthesized. The new compounds were characterized by NMR, FT-IR and ESI-MS methods. PM3 semiempirical calculations of molecular structures and the heats of formation of compounds P13–P18 were also performed. Critical micellization concentrations (CMCs) were determined to characterize the aggregation behavior of the new BAC analogues. The antimicrobial properties of novel QACs were examined by determining their minimal inhibitory concentration (MIC) values against the fungi Aspergillus niger, Candida albicans, Penicillium chrysogenum and bacteria Staphylococcus aureus, Bacillus subtilis, Escherichia coli and Pseudomonas aeruginosa. The MIC values of N,N-dimethyl-N-(4-methylpyridyl)-N-alkylammonium chlorides for fungi range from 0.1 to 12 mM and for bacteria, they range from 0.02 to 6 mM.